Desperately seeking the African personality! van Niekerk, E (1996) Paradigms of mind: Personality perspectives in context. Johannesburg: International Thomson Publishing (Southern Africa) 263 pages - Gillmer, Bruce (PINS-Psychology in Society, 2026)
There have been at least three recent attempts to produce an introductory text on personality for and about South Africans Andre Moller's edited collection, previously reviewed (Gillmer, 1996) in this journal, Meyer, Moore, and Viljoen's (1997) revamped and hideously renamed earlier edition of their widely prescribed Personality theories: From Freud to Frankl; and now van Niekerk's serving of trendy brutalism personality a la Kuhn. This Is by far the worst of the three because it fails to provide - as the others do, but far more glaringly - either an African perspective or the "paradigms" in the vanguard of contemporary personality "science".